Pengukuran Indeks Kepuasan Masyarakat Terhadap Pelayanan Di Badan Perencanaan Pembangunan, Penelitian dan Pengembangan Daerah Tahun 2020 - Ade Tahyan Alimudin (KarismaPro, 2020)
The size agreed upon by the assistant is determined by the level of service recipient satisfaction. The satisfaction of beneficiaries received must be in accordance with what is needed and expected. And the government has also issued a Regulation of the Minister of Administrative Reform and Bureaucratic Reform No. 14 of 2017 concerning Guidelines for Surveying Public Satisfaction of Public Service Providers. The Elements That Are Focused In The Community Satisfaction Survey consist of 9 Elements. Of the 9 non-services in the work unit of the Regional Development Planning, Research and Development Agency in the City of Tasikmalaya in general, the Highest Average Value (NRR) The Highest Non-Service Cost Conformity (3.59), While No one has an Over Value (NRR) that almost the same but still in the GOOD category. The element with the lowest average value (NRR) is service time (average 3.07). This value reflects the highest level of satisfaction obtained from the Conformity of Service Costs. While at the time of service provides the lowest level of satisfaction. Everyone's Average Rating. Successful researcher so that BAPPELITBANGDA of Tasikmalaya City needs to strive for and maintain good service quality, as well as improve socialization for service recipients regarding the requirements and time of development planning services.The size agreed upon by the assistant is determined by the level of service recipient satisfaction. The satisfaction of beneficiaries received must be in accordance with what is needed and expected. And the government has also issued a Regulation of the Minister of Administrative Reform and Bureaucratic Reform No. 14 of 2017 concerning Guidelines for Surveying Public Satisfaction of Public Service Providers. The Elements That Are Focused In The Community Satisfaction Survey consist of 9 Elements. Of the 9 non-services in the work unit of the Regional Development Planning, Research and Development Agency in the City of Tasikmalaya in general, the Highest Average Value (NRR) The Highest Non-Service Cost Conformity (3.59), While No one has an Over Value (NRR) that almost the same but still in the GOOD category. The element with the lowest average value (NRR) is service time (average 3.07). This value reflects the highest level of satisfaction obtained from the Conformity of Service Costs. While at the time of service provides the lowest level of satisfaction. Everyone's Average Rating. Successful researcher so that BAPPELITBANGDA of Tasikmalaya City needs to strive for and maintain good service quality, as well as improve socialization for service recipients regarding the requirements and time of development planning services.